1997
DOI: 10.1097/00001756-199703030-00013
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in nitrite/nitrate levels and antioxidant defense in rat brain

Abstract: This study assessed sex differences in stable metabolites of nitric oxide and major enzymes involved in antioxidant defense in various regions of rat brain. Nitrite/nitrate levels and activities of superoxide dismutase and catalase were determined in cortex, hippocampus, corpus striatum, midbrain and cerebellum of adult male and female Sprague-Dawley rats. Nitrite/nitrate levels were significantly higher in the cortex and the hippocampus of male than female rats, while catalase activity was higher in the corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 20 publications
3
29
0
2
Order By: Relevance
“…Furthermore, Thorup et al (1999) have shown that picomolar concentrations of CO, in renal resistance arteries from rats, facilitate the release of NO from a large intracellular pool, whereas micromolar concentrations of CO inhibit NOS activity and NO generation. Our results, in accordance with our previous findings, showed that while NO 2 À +NO 3 À levels were higher in the male hippocampus than the female (Taskiran et al, 1997), CO treatment had no effect on total NO 2 À +NO 3 À levels both in the male and female rat brain. Although this finding is not consistent with some of the previous studies mentioned above, it may be explained by the observation of Stamler and Piantadosi (1996).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, Thorup et al (1999) have shown that picomolar concentrations of CO, in renal resistance arteries from rats, facilitate the release of NO from a large intracellular pool, whereas micromolar concentrations of CO inhibit NOS activity and NO generation. Our results, in accordance with our previous findings, showed that while NO 2 À +NO 3 À levels were higher in the male hippocampus than the female (Taskiran et al, 1997), CO treatment had no effect on total NO 2 À +NO 3 À levels both in the male and female rat brain. Although this finding is not consistent with some of the previous studies mentioned above, it may be explained by the observation of Stamler and Piantadosi (1996).…”
Section: Discussionsupporting
confidence: 93%
“…in the presence of NADPH. NO 2 À levels were determined spectrophotometrically by the Griess reaction (Giovannoni et al, 1997;Taskiran et al, 1997). Sodium nitrate solutions were used for standard measurements.…”
Section: Uptake Assaysmentioning
confidence: 99%
“…This mixture was then centrifuged at 3000Â g for 20 min and the supernatants were used for the assays as described previously. 21,22 Light Microscopy…”
Section: Determining the Tissue Total No(no X ) Levelsmentioning
confidence: 99%
“…Nitrite plus nitrate (NOx) which are the last and stabile products of NO were determined in tissue samples spectrophotometrically (21).…”
Section: Nox Assaymentioning
confidence: 99%